The relationship between work environment and job performance among support staff in selected government offices in Maran, Pahang Darul Makmur / Fatin Awani Zainudin - Zainudin, Fatin Awani (Faculty of Business and Management, 2018)
The purpose of this research was to investigate the correlation between work environment and job performance among support staff in selected government offices in Maran, Pahang Darul Makmur. This correlational study used a stratified disproportionate sampling technique and the sample size was determined using Krejcie and Morgan (1970). Survey questionnaires were distributed to 123 respondents who worked as support staff and yield 100% response rate. Majority of the respondents were female, aged 31 to 40 years old and from grade C. Many of them were from Majlis Daerah Maran. The findings showed that there was a strong relationship between work environment and job performance (r= 0.62, p=O.OO). The value of R-Square showed that only 42.9% of the variance in work environment can be predicted from the variables of lighting and work stress. The multiple regression model produced F (2, 120) =0.00, p<.05. The correlation result also showed medium and strong significant relationships between lighting (r=.39), work stress (r=.62) and job performance. Moreover, the mean showed the result for independent variable which are lighting (M=4.11, SD=.60) and work stress (M=3.99, SD=.65). It is recommended that managers should improve the workstation personalization, improve work environment and adjust employees' work load. Future research should focus on private sector and study other independent variables such as workplace layout, noise, air quality and include different level of thought between top management and support staff.